IMPROVING STUDENT’S DISCIPLINE THROUGH THE BEHAVIORIST LEARNING THEORY APPROACH AT SMA X IN ENDE REGENCY - Bonaventura R. Seto; Laurensia Silvia Rara (SOSIOEDUKASI, 2026)
Student discipline is one of the important factors that influences the success of the educational process. This study aims to describe students’ disciplinary problems and analyze the implementation of a psychopedagogical approach based on behaviorist learning theory in improving students’ discipline at SMA X in Ende Regency. This study employed a qualitative descriptive approach conducted during the second semester of the 2024/2025 academic year. The research participants consisted of one guidance and counseling teacher, one principal, two homeroom teachers, eight students with a history of disciplinary violations, and five parents selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Sandal. The findings revealed that students’ disciplinary problems included tardiness, truancy, violations of school regulations, the use of mobile phones during learning activities, leaving the classroom without permission, and bullying behavior. The guidance and counseling teacher implemented behaviorist interventions including individual counseling, behavior shaping, behavior contracts, positive reinforcement, classroom guidance, home visits, and collaboration with parents.